(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Raspberry Pi and its editions have brought with them an aura of amendment in the global of embedded structures. With their amazing computation and verbal exchange capabilities and low footprint, these gadgets have thrown open the chance of figuring out a network of things at some stage in a very fee-efficient manner. At the same time as such networks offer accurate solutions to super issues, they may be honestly a long way from being clever. Most of the currently available implementations of one of these community of gadgets involve a centralized cloud-based totally server, which helps to make the necessary sensible selections, leaving those devices underutilized. Although this paradigm offers a quick and easy solution, it has limited scalability, is less robust and sometimes proves costly. As the technology increases day by day there came many changes even in the home automation system in the present-day world and everything can be managed with the help of raspberry pi. This paper presents a minicomputer using Raspberry Pi which can play videos, power point presentation.